Sesamin alleviates defects in seizure, behavioral symptoms, and hippocampus electroencephalogram in a pentylenetetrazol rat model - Farima Malekinia; Yaghoob Farbood; Alireza Sarkaki; Seyed Esmaeil Khoshnam; Seyedeh Parisa Navabi (Iranian Journal of Basic Medical Sciences, 2023)
Objective(s): Seizure is a prevalent disorder reflected by powerful and sudden activity of neural networks in the brain that leads to tonic-clonic attacks. These signs may be due to an increase in excitatory/inhibitory neurotransmitters ratio. So, the current experiment aimed to examine the seizure and neurobehavioral parameters, as well as the hippocampus local electroencephalogram (EEG) after seizure with and without sesamin pretreatment.   Materials and Methods: Sesamin (15, 30, and 60 mg/kg/5 ml, intraperitoneal or IP, vehicle: dimethyl sulfoxide or DMSO, for 3 days) was administrated before pentylenetetrazol (PTZ) (60 mg/kg/10 ml, IP, vehicle: saline), which induces acute seizure in adult male Wistar rats (230 ± 20 g, six weeks old). Different phases of seizures (score, latency, duration, and frequency), behavioral parameters (passive avoidance memory, anxiety, and locomotor activity), and hippocampus local EEG were evaluated after the injections. At the end of the experiments, oxidative stress markers plus gene expression of phosphoinositide 3-kinase/protein kinase B or PI3K/Akt mRNA were measured in the hippocampus.  Results: Pretreatment with sesamin (30 mg/kg) could significantly decrease seizure scores and oxidative stress in the hippocampus. PTZ injection induced EEG deficits and neurobehavioral impairments which were significantly decreased by sesamin, especially in Beta, Theta, and delta EEG waves.  Also, the expression of PI3K/Akt significantly increased in the sesamin (30 mg/kg) group in comparison with the PTZ group. Conclusion: Sesamin could prevent seizure attacks and neurobehavioral and EEG deficits induced by pentylenetetrazol, probably through the PI3K/Akt signaling pathway.